Intracranial stereotactic radiosurgery - Lunsford, L. Dade; Sheehan, Jason P. (Thieme, 2016)
Written by international experts in the fields of neurosurgery, neurology, physics, and radiation oncology, many of them pioneers in radiosurgery, the book is a concise yet comprehensive reference on current techniques for radiosurgery of the brain and all the contextual information needed to understand why and how these current techniques are used, such as the evolution of the radiosurgery modality, the sciences of radiosurgery such as physics and radiobiology, and the devices/technology systems used. The core of the book is the detailed discussion of radiosurgical procedures for specific pathologies and disorders, such as arteriovenous malformations, meningiomas, pituitary adenomas, movement disorders, gliomas, ocular disorders, and obsessive compulsive disorder. These chapters address the benefits and limitations of radiosurgical techniques for each indication and describe the outcomes, possible complications and their management, and alternative treatments